2020
DOI: 10.1177/1369433220949464
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the flexural behavior of local prestressed steel–concrete composite continuous box beams

Abstract: The flexural bearing capacities of three composite continuous box beams with different prestressing degrees were tested and studied to investigate the influences of local prestressing bundles on the deflection, relative slip of interface, strain, and redistribution of the internal force of the steel–concrete composite continuous box beam. Results show that the arrangement of local prestress can not only improve the bending stiffness at the mid-span of the composite continuous box beam, but also significantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Based on the experiment of Zhang et al [ 22 ], nine 1:8-scaled models of continuous composite box beams were fabricated according to the Chinese code (JTG 3362-2018) [ 28 ]. FSCB-0 was used for the static comparison test, and FSCB-1 to FSCB-8 were used for the fatigue tests.…”
Section: Experimental Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the experiment of Zhang et al [ 22 ], nine 1:8-scaled models of continuous composite box beams were fabricated according to the Chinese code (JTG 3362-2018) [ 28 ]. FSCB-0 was used for the static comparison test, and FSCB-1 to FSCB-8 were used for the fatigue tests.…”
Section: Experimental Testmentioning
confidence: 99%
“…Previous studies have shown that the formation of the plastic hinge will cause obvious internal force redistribution at the middle support of continuous composite box beams [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Table 6 shows the measured force (not including self-weight) at the middle support under the target number of loading cycles, with an applied static load of 340 kN.…”
Section: Analysis and Calculation Of Internal Force Redistributionmentioning
confidence: 99%
See 1 more Smart Citation